Training of Trainers: The Post-Graduate Diploma In Teaching And Learning Program at Universiti Malaysia Sarawak - Peter, Songan; Gabriel Tonga, Noweg; Fitri Suraya, Mohamad (Researchgate, 2004)
A public university in Malaysia is generically geared towards three core businesses, namely teaching-learning, research, and consultancy and community services. Being a young university in the country and the first one in the state of Sarawak, UNIMAS has had to hire young graduates to put together eight faculties at the time it opened its doors to the first intake of students in 1994. The more experienced faculty members are lecturers who have taught elsewhere in Malaysia, mostly with more than five years of teaching experience at university level. As the academic community at the university grew, and as the student population increased each year, the university realized how much the quality of teaching-learning needed to be effectively addressed, in terms of training and recognition. The university acknowledged the necessity to put in place a mechanism to train lecturers the basics of teaching, to ensure effective learning and the achievement of learning outcomes, as part of the contribution to a quality education at the university. It is also hoped that, with the current fresh interest in upgrading the skills of teaching among lecturers, the academic community will collectively be more inclined toward improving the delivery of learning and skills in their courses. After a decade of existence, the university introduced a special training program—the Postgraduate Diploma in Teaching and Learning as a strategy to fulfill its mission to achieve excellence in teaching, research, and scholarship. As one of the youngest universities in the country, UNIMAS is now at a crucial stage of seriously considering developing a culture to enhance the scholarship of teaching and learning to provide quality education.